Vase life extension and chlorophyll fluorescence yield of bougainvillea flower as influenced by ethanol to attain maximum environmental beautification as ornamental components - Hossain, A.B.M.S.; Boyce, A.N.; Majid, H.M.A. (2008)
The study was conducted to investigate the effect of ethanol at different concentrations (ET) on bougainvillea flower longevity and delay senescence in storage condition. The treatments were water control, 2 ET, 4 ET, 8 ET, 10 ET, 20 ET, 30 ET, 40 ET, 50 ET and 70 ET. Flower longevity was 2 days more in 4, 8 and 10 ethanol than water control and other concentrations of ethanol. Petal wilting and senescence were occurred 2 days later in 4, 8 and 10 ET than in water control. Percent petal's color changed was later in water 4, 8 and 10 than in control, 2, 20, 30, 40, 50 and 70 ET. Chlorophyll fluorescence intensity (photosynthetic yield) followed by time (ms) at different ethanol concentrations was higher in 4, 8 and 10 ET than in water control and other concentrations. Fo (lower fluorescence) was lower in 4, 8 and 10 ET than in water and other concentrations. However, Fm and Fv (higher fluorescence and relative variable fluorescence (Fm-Fo) were higher in 4, 8 and 10% ET than in other ET concentrations. Fv/Fm (quantum yield or photosynthetic yield) was higher in 4, 8 and 10% ET than in other ET concentrations. The result showed flower vase life was significantly affected by ethanol concentrations and longevity was higher in 4, 8 and 10% ethanol than in water control and other concentrations. Â© 2008 Science Publications.